Ketersediaan koleksi Perpustakaan SMA 3 Depok dalam menumbuhkan minat baca - Talita, Talita; Rachmawati, Tine Silvana; Rizal, Edwin (Jurnal Kajian Informasi dan Perpustakaan, 2017)
The existence of school libraries can provide benefits for students to search for the information needed, as a place to work on their tasks, looking for entertaining reading materials or just to fill their spare time while on a break. The school library becomes to foster students reading interest if the collection is adapted to the students needs. The SMA 3 Depok Library is a school library that has a library collection from fiction and non-fiction. Therefore, this study aimed to identify the availability of library collections which included the relevance and completeness of collections, and the collection updates in order to foster studentsâ interest in reading. The research method used the quantitative method through descriptive survey conducted on students of class XI SMA 3 Depok, with a population of 408 students. The sampling technique used in this study was simple random sampling with a total sample of 81 students. Data were obtained through a questionnaire, observation, interview, and literature study. The result of this research indicated, the library collection was quite relevant, the collection of books fulfilled the completeness of the collection, however the non-book collection did not exist yet; moreover, the library collection was in accordance with the latest development of knowledge. So, based on the three indicators previously mentioned, SMA 3 Depok studentsâ reading interest has developed which is shown by the high frequency of reading interest. The library in 3 SMA in Depok should be provided with adequate facilities to support the use of library collections.